Experimental and numerical studies of pressure and gap length effects on energy deposition in spark discharge - Korytchenko, K.V.; Varshamova, I.S.; Meshkov, D.V.; Dubinin, D.P.; Kovalenko, R.I.; Nazarenko, S.Yu. (Вопросы атомной науки и техники, 2021)
A study of the influence of the discharge gap length and the initial gas pressure on the energy deposition into the discharge channel was done. The study was conducted at the same total discharge energy. It is experimentally shown that the connection of the voltage probe to the discharge circuit significantly affects the discharge current. The determination of the energy deposited into the spark channel is based on the results of numerical simulation of the spark channel development. Experimentally measured discharge currents at different pressures and the gap length were used as initial data for the calculation. Based on the obtained results, it is determined which of the factors (the initial pressure or the gap length) has the strongest influence on the energy input into the spark channel. Проведено дослідження впливу довжини розрядного проміжку та початкового тиску газу на введення енергії в розрядний канал. Дослідження проведено за однакової повної енергії розряду. Експериментально показано, що підключення дільника напруги до розрядного ланцюга суттєво впливає на розрядний струм. Визначення енергії, що вводиться в іскровий канал, здійснено за результатами чисельного моделювання розвитку іскрового каналу. Як вихідні дані для розрахунку використано експериментально виміряні розрядні струми при різних тисках та довжинах розрядного проміжку. На підставі отриманих результатів визначено, який з чинників (початковий тиск або довжина проміжку) більше впливає на введення енергії в іскровий канал. Проведены исследования влияния длины разрядного промежутка и начального давления газа на введение энергии в разрядный канал. Исследования проведены при одинаковой полной энергии разряда. Экспериментально показано, что подключение делителя напряжения к разрядной цепи существенно влияет на разрядный ток. Определение энергии, вводимой в искровой канал, осуществлено по результатам численного моделирования развития искрового канала. В качестве исходных данных для расчета использованы экспериментально измеренные разрядные токи при различных давлениях и длинах разрядного промежутка. На основании полученных результатов определено, какой из факторов (начальное давление или длина промежутка) больше влияет на ввод энергии в искровой канал.